Respuesta :

Answer:

A

Step-by-step explanation:

To simplify the expression multiply the numerator and denominator by the conjugate of the denominator.

Note that i² = - 1

The conjugate of 6 - 4i is 6 + 4i , then

= [tex]\frac{(4-3i)(6+4i)}{(6-4i)(6+4i)}[/tex] ← expand numerator./ denominator using FOIL

= [tex]\frac{24+16i-18i-12i^2}{36+24i-24i-16i^2}[/tex]

= [tex]\frac{24-2i+12}{36+16}[/tex]

= [tex]\frac{36-2i}{52}[/tex]

= [tex]\frac{2(18-i)}{52}[/tex]

= [tex]\frac{18-i}{26}[/tex] → A

ACCESS MORE